Teknologi Geolocation Berbasis Android dengan Metode K-Means untuk Pemetaan UMKM di Kabupaten Jepara - Azizah, Noor; Widiastuti, Nur Aeni (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
Micro, Small and Medium Enterprises (MSMEs) are industrial sectors that are very important to sustain the economy of Jepara Regency. There are 18,695 Small and Medium Enterprises (SMEs) in Jepara Regency in 2016, including wood carving, troso weaving, chopper brass (monel) jewelry, sculpture, rattan crafts, calligraphy, and reliefs. The number of SMEs in Jepara makes buyers or tourists have many choices in buying products of varying quality and competitive prices. In addition, sometimes they are also confused in finding the location of SMEs. Therefore, this application is made to solve these problems by making an application that provides location-based information center industrial services. This application is expected to facilitate tourists in finding the location of the industry to be addressed. Geolocation technology is used to identify real-world geographic locations that can be applied to the Android operating system. So this application provides store description services, product photos, and maps. SMEs are presented in the application in the map using the k-mean algorithm. The parameters used are the type of industry, number of employees, turnover per year, tools used. For the clustering have 3 categories, there are namely small, medium and large. The advantages of this algorithm can group data according to the similarity of data used in one group and minimize the same data between groups and cannot process data that is a missing value.